SCIDOT-45. MAGNETIC FIELD STRUCTURE OF THE HÆLO™ PEDIATRIC SYSTEM. (11th November 2019) - Peterson, Eric; Figueroa, Xavier; Butters, Mike; Woodcock, Amanda; Brown, Dan; Ferguson, Ken
Abstract: BACKGROUND: The Hælo pediatric system, an investigational medical device intended to treat diffuse midline glioma (DMG), emits a magnetic field intended to disrupt the growth of DMG tumors. The Hælo headcoil is positioned on the back of the patient's head; the field envelopes the patient's head and the specific frequencies of the field penetrate the skull and brain tissue without any significant attenuation. METHODS: The shape and intensity of the magnetic field emitted by the Hælo headcoil were measured using a triaxial magnetic sensor, which measures the flux density along three orthogonal axes. The headcoil is designed to conform to the back of the head and is not planar. To account for the slight difference in field shape due to the coil's convex shape, the field was measured with the coil held in both a convex and concave position relative to the central plane. A custom-designed measurement system was used to position the sensor in a three-dimensional grid with 1 cm resolution (approximately 10, 000 individual measurements for each coil position.) A test field with the same flux density produced by the Hælo pediatric system treatment field was used. The root mean square of the field along each axis was calculated and combined to yield the total flux density at each position. The datasets from each coil position were combined to create a complete three-dimensional map of the field generated by the headcoil. RESULTS: The greatest flux density is proximal to the coil. The test field ranged from approximately 200 mGauss near the headcoil to 100 mG within the ellipsoid formed by the headcoil. CONCLUSION: The field of the Hælo pediatric system encompasses the brain and portions of the brainstem, and thus delivers a targeted magnetic therapeutic to the common tumor locations for DMG.